Active derivatives based on D-galactose and D-lactose in synthesis of neoglycoconjugates - L. Yu. Guryeva; A. A. Severyanova; Y. L. Sebyakin (Тонкие химические технологии)
Synthesis of active derivatives of carbohydrates D-galactose and D-lactose and neoglycoconjugates on their basis is carried out. For receiving modified glycolipids the approach with use N-hydroxysuccinimide ethers of carbohydrates is offered.